The Prospects and Challenges of STEM-PjBL with Design Thinking Strategies in Enhancing Students' Creativity and Entrepreneurial Thinking in the Context of Plastic Waste Recycling: Teachers' Perspectives - Kenny Rama Dhany; Dwi Yulianti; Abdurrahman (Jurnal Penelitian Pendidikan IPA, 2025)
This STEM education a new trend of learning innovation. However, there are still many students who have not received integrated STEM education that focuses on developing 21st century skills. So that efforts to create learning innovations with a STEM approach become a challenge for teachers at every level of education, including in elementary schools. This study aims to explore teachers' views and challenges of integrated STEM learning Projecj-Based Learning (PjBL) with Design Thinking strategy and its potential in stimulating creative thinking and entrepreneurship. This study used the Cross-Sectional Survey methodology Explanatory Mixed Method design that has involved 250 elementary school teachers in Lampung Province. The results showed that most elementary school teachers do not have sufficient knowledge on how to develop STEM-PjBL learning innovation scenarios, especially in integrating Design thinking strategies in an effort to stimulate students' creative thinking and entrepreneurial skills. However, they believe that STEM-PjBL integrated with Design Thinking will provide learning experiences that stimulate students to think (minds-on) and be actively involved in project completion (hands-on). In addition, they also think that STEM-PjBL has the potential to prepare students to have a number of creative spaces and habituation in the classroom, especially in recycling plastic waste.